2021
DOI: 10.3748/wjg.v27.i25.3925
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection vs endoscopic mucosal resection for colorectal polyps: A meta-analysis and meta-regression with single arm analysis

Abstract: BACKGROUND Endoscopic submucosal dissection (ESD) has shown to be effective in management of colorectal neoplasm in the Asian countries, while its implementation in Western countries where endoscopic mucosal resection (EMR) is preferred is still debatable. AIM To compare the surgical, histological, and oncological outcomes between ESD and EMR in the treatment of colorectal polyps, with subgroup analysis comparing the efficacy of ESD and EMR between Japan and the rest of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…When standard EMR without routine margin ablation is used, we found a 12-month recurrence rate of 15.2%. This is comparable to the results found in the two available meta-analyses published in 2014 and 2021, which reported recurrence rates of 15%[ 6 ] and 10%[ 23 ], respectively. However, since then, many new or modified endoscopic removal techniques have been developed.…”
Section: Discussionsupporting
confidence: 89%
“…When standard EMR without routine margin ablation is used, we found a 12-month recurrence rate of 15.2%. This is comparable to the results found in the two available meta-analyses published in 2014 and 2021, which reported recurrence rates of 15%[ 6 ] and 10%[ 23 ], respectively. However, since then, many new or modified endoscopic removal techniques have been developed.…”
Section: Discussionsupporting
confidence: 89%
“…A piecemeal technique was utilized in 20 of 22 patients who had residual polypoid tissue. ESD is associated with a lower rate of recurrence as compared to EMR, but ESD is a labor-intensive and technically difficult procedure associated with a higher perforation rate [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vascular anatomy of the right colon has showed several significant changes, including the absence of some branches (lack of RCA in 27.4% of cases), extra branches, common trunk, and posterior superior mesenteric vein routes [ 33 ]. Therefore, most studies indicate that the proximal ileum resection margin for right colon cancer should be 5–10 cm from the tumor margin [ 34 ]. In this study, we have demonstrated that terminal ileum lymph node metastasis is related to tumor location ( χ 2 = 6.273, p = 0.043).…”
Section: Discussionmentioning
confidence: 99%